Bee inspired QoS routing in VANET - Jung, L.T. (Institute of Electrical and Electronics Engineers Inc., 2014)
A bee communications inspired QoS routing scheme is proposed in this paper primarily to improve the network throughput and to reduce packet loss in vehicular ad hoc network (VANET) environment. The proposed scheme is inspired by the natural bee communications paradigm. The mobile agent concept is adopted from the bees' mobility behavior for network traffic information exchange among the VANET nodes aiming for a quality transmission of data packets. This is accomplished by calculating the corresponding QoS provision values based on certain QoS metrics threshold to determine a reliable and stable route between a source (beehive) and the destination (food source) node. The proposed scheme shows a better performance as compared to the AODV and DSR protocols in terms of packet loss and network throughput. Â© 2014 IEEE.